Genealogies And Archives Of The Possible - Federica Giardini (Soft Power, 2024)
This is a particularly interesting text, not only for its opening up of research perspectives, but also —and this is something I would like to emphasize— for the way it contributes to the definition of the tasks of political philosophy in its specificity. A first contribution in this direction comes from the genealogical approach that was adopted. References to Michel Foucault’s research are anything but occasional —I recall, for example, the recent article devoted to the theme of labour in Foucault’s Truth and Juridical Forms and The Use of Pleasure (Faitini, 2022)— both in method and, conversely, in the original choice to distance herself from some analyses of the contemporary that use Foucauldian categories. Indeed, the author declares that she does not want to “equate ethics, governmentality and ideology” (Faitini, 2023, p. 32), thus grasping a limitation of those critical theses that, while moving away from the intention of clarifying the dynamics of the contemporary, end up producing a reinforcement of the iron cage in which we would find ourselves.